Simulasi Performa Mekanik Jarum Mikro Berbahan Tembaga Menggunakan Perangkat Lunak ANSYS - Retno Maharsi; Aidah Rohmah; Tata Widyawasih; Damianus Dinata Putra; Sabrina Milesa; Doni Bowo Nugroho; Amrina Mustaqim (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2025)
Microneedles are a minimally invasive transdermal technology that has been widely explored in biomedical applications. Copper (Cu) is a promising material for microneedles due to its favorable mechanical properties and inherent antimicrobial effects. However, numerical studies on the structural performance of copper microneedles remain limited. This study aims to evaluate the mechanical response of solid copper microneedles using finite element analysis (FEA) in ANSYS Workbench. A 3D conical microneedle model with a height of 1000 µm was subjected to external pressures ranging from 400 to 1000 MPa. Four key parameters—total deformation, equivalent stress, maximum principal stress, and structural error—were assessed under two mesh densities (coarse and fine). Simulation results indicate that the fine mesh yields more accurate and stable stress and deformation distributions compared to the coarse mesh. Additionally, the fine mesh better captures peak stress concentrations, which are critical for evaluating microstructural failure. These findings underscore the importance of mesh selection in numerical simulations and provide a foundation for the preliminary design of copper-based microneedles for medical applications.